Аналіз та дослідження ефективності використання нових методів еліптичного скалярного множення - Танцура, Д. В. (ХНУРЭ, 2009)
During realization of electronic digital signature (DSA) standards, using cryptotransformation in the groups of points of elliptic curves (EC), are more frequent than all used in the modern systems of defence of commercial and other valuable information.